SAE Technical Paper Series 2013
DOI: 10.4271/2013-01-0463
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Underbody Roughness on Rear Wake Structure of a Squareback Vehicle

Abstract: In this paper the effects of a rough floor on the rear wake structure of a simplified squareback model (the Windsor model) is investigated using balance, base pressure measurements and two and three component planar PIV. The work forms part of a larger study to develop understanding of the mechanisms that influence overall base pressure and hence the aerodynamic drag. In the work reported in this paper the impact of a rough floor on the base pressure and wake flow structures is quantified at three different ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The location of these perturbations varies from upstream of the base of the geometry (inflow conditions (Kang et al 2021), asymmetric boat-tailing/tapering (Bonnavion & Cadot 2019;Pavia, Passmore & Varney 2019), yaw (Cadot, Evrard & Pastur 2015;Li et al 2019) or pitch (Bonnavion & Cadot 2018)) to the base of the geometry (pulsed jets (Li et al 2016), active flaps (Brackston et al 2016)). An important subset of asymmetric perturbations is located between the underside and the ground, for example ground clearance (Grandemange, Gohlke & Cadot 2013a), the ratio of the underbody velocity to free-stream velocity (Castelain et al 2018) and underbody roughness (Perry & Passmore 2013). The importance of this subset lies in their frequent encounters under real road conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The location of these perturbations varies from upstream of the base of the geometry (inflow conditions (Kang et al 2021), asymmetric boat-tailing/tapering (Bonnavion & Cadot 2019;Pavia, Passmore & Varney 2019), yaw (Cadot, Evrard & Pastur 2015;Li et al 2019) or pitch (Bonnavion & Cadot 2018)) to the base of the geometry (pulsed jets (Li et al 2016), active flaps (Brackston et al 2016)). An important subset of asymmetric perturbations is located between the underside and the ground, for example ground clearance (Grandemange, Gohlke & Cadot 2013a), the ratio of the underbody velocity to free-stream velocity (Castelain et al 2018) and underbody roughness (Perry & Passmore 2013). The importance of this subset lies in their frequent encounters under real road conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Typical passive methods such as side tapering [4,5], roof tapering [4,6,7,8,9], roughness strips [10] and underbody tapering [11,12] have all been shown to result in base drag reductions. Active methods have also been tested with drag reductions being reported but little shown in terms of net energy reduction (as the systems require energy input); these include rolling trailing and leading edges [13], blowing [14] and thermal riblets [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that changing the size and shape of this wake structure can increase the base pressure and thereby reduce the pressure drag. Many previous studies have demonstrated the effects of passive elements such as splitter plates and base cavities (Duell and George 1993), passive base bleed (Brown et al 2010), base slats (Littlewood et al 2011), forebody roughness (Van Raemdonck and Van Tooren 2008), underbody roughness (Perry and Passmore 2013) and base flaps (Grandemange et al 2013c). Research has also been conducted into several active flow control techniques such as suction (Rouméas et al 2009b), blowing (Littlewood and Passmore 2012), oscillated suction and blowing (Kim et al 2004) and moveable vortex…”
mentioning
confidence: 99%